The psychology of work : theoretically based empirical research - Hulin, Charles L., 1936-; Brett, Jeanne M.; Drasgow, Fritz (Organization and management series (Routledge (Firm)), 2002)
This edited volume is derived from a conference held in honor of Charles Hulin's contribution to the psychology of work. His research has carefully developed and tested theory related to job satisfaction, withdrawal from work, and sexual harassment. Edited by Hulin's students, The Psychology of Work discusses research in job satisfaction. This research shows that job satisfaction plays an essential role in theories of organizational behavior. Formal models are used, such as item response theory, structural equation modeling, and computational models. Three general and consiste.